PERAN KERJASAMA DENGAN DUNIA USAHA DAN INDUSTRI DALAM MENINGKATKAN KUALITAS LULUSAN SMK BERBASIS PESANTREN - Nur Azizah, Rahma Nanda; Aimah, Siti (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
Cooperation between Vocational High Schools (SMK) and the Business World and Industry (DUDI) is an important strategy in improving the quality of graduates to meet the needs of the workforce. This study aims to examine the role of cooperation between Islamic boarding school-based Vocational High Schools (SMK) and the business world and industry (DUDI) in improving the quality of graduates. The main problem raised is the gap between graduate competencies and the increasingly dynamic needs of the industry, especially in Islamic boarding school-based education that combines vocational and Islamic curriculum. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies at 3 Islamic boarding school vocational schools that are industry partners in Banyuwangi Regency. The results of the study indicate that strategic collaboration with DUDI has a positive impact on improving technical skills, discipline, and work readiness of graduates. The integration of Islamic boarding school values provides superior work ethics that are an added value in the eyes of the industry. Further findings state that the challenges of limited facilities, lack of linkage and match of the curriculum, and suboptimal communication are still obstacles